2019
DOI: 10.1093/ibd/izz164
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of High Dose Influenza Vaccine for Patients with Inflammatory Bowel Disease on Anti-TNF Monotherapy: A Randomized Clinical Trial

Abstract: Background Patients with inflammatory bowel disease (IBD) on anti-tumor necrosis factor alpha (TNF) agents may have lower immune response to the influenza vaccine. We aimed to evaluate the immunogenicity of the high dose (HD) vs standard dose (SD) influenza vaccine in patients with IBD on anti-TNF monotherapy. Methods We performed a randomized clinical trial at a single academic center evaluating the immunogenicity of the HD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 29 publications
2
62
0
3
Order By: Relevance
“…Current evidence does not support the use of immunomodulatory agents combined with ustekinumab [ 17 ]. Similar to our results in the ustekinumab group, a recent study showed that immune responses to influenza vaccination in patients treated with vedolizumab, a monoclonal antibody against the α4ÎČ7 integrin, were not altered either [ 40 ]. Interestingly, the immune response to an enterally administered vaccine was impaired during treatment with vedolizumab, possibly reflecting the gut-selective action of this therapy [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Current evidence does not support the use of immunomodulatory agents combined with ustekinumab [ 17 ]. Similar to our results in the ustekinumab group, a recent study showed that immune responses to influenza vaccination in patients treated with vedolizumab, a monoclonal antibody against the α4ÎČ7 integrin, were not altered either [ 40 ]. Interestingly, the immune response to an enterally administered vaccine was impaired during treatment with vedolizumab, possibly reflecting the gut-selective action of this therapy [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…A booster vaccination failed to show better protection rates [ 7 , 39 ] and timing relative to infliximab infusion neither showed to affect serological protection [ 13 ]. Recently, a study found that four times higher dose vaccination resulted in higher antibody responses to influenza vaccination compared to the standard dose, without leading to more adverse effects [ 40 ]. Yet, “high dose” vaccination is currently only recommended by American guidelines for patients aged 65 years or older [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that immune response to pneumococcal polysaccharide vaccination (PSV-23) is impaired in Crohn's disease (CD) patients on combination of TNF-blockers and immunomodulators (3) and that the serologic conversion rate to influenza vaccine is lower in immunossupressed IBD patients (4,5) . On the other hand, treatment with ustekinumab or vedolizumab does not appear to reduce responses to flu vaccine (6,7) .…”
Section: Does Immunosuppression Affect the Effectiveness Of Covimentioning
confidence: 90%
“…There are studies which have analyzed the high-dose influenza vaccines, which contain four times more hemagglutinin than the standard dose vaccine. A study showed that patients with IBD treated with anti-TNF monotherapy receiving high-dose influenza vaccine had significantly higher seroprotection than standard dose vaccines [24]. The inactive influenza vaccine is safe in patients with IBD on immunosuppressants, with minimal-vaccine associated local reactions without any increase in IBD flares [25].…”
Section: Influenza Vaccinementioning
confidence: 99%